Quality Management In Semarang District Early Childhood Education Institutions - Dewi, Nufitriani Kartika; Wasino, Wasino; Utomo, Cahyo Budi; Yuwono, Agus; Fauziah, Syifa (Universitas Negeri Semarang, 2024)
This research explores the implementation of Quality Management in Early Childhood Education (ECE) institutions in Semarang Regency with a focus on the Merdeka Belajar Curriculum. Based on the policy of the Ministry of Education, Culture, Research, and Technology, this curriculum provides flexibility to ECD institutions to choose teaching tools that suit the needs and characteristics of learners, with the aim of improving the quality of learning in the 2022-2024 recovery period. This research used a qualitative approach with a case study method, focusing on an ECD Institution Unit in Semarang Regency. Data were collected through observation, interviews, and documentation, with data validity testing using triangulation. The results showed that the implementation of Quality Management in Merdeka Belajar Curriculum in Semarang Regency includes aspects of curriculum planning, implementation, organization, and monitoring and evaluation. Strengths involve teacher flexibility in choosing learning methods, while weaknesses involve challenges in the organization of learning resources. This research provides a comprehensive picture of the dynamics of Quality Management in Semarang Regency PAUD institutions, providing a deeper understanding of the implementation of Merdeka Belajar Curriculum. The implications include contributions to the development of more effective, responsive, and quality early childhood education in the region.